(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the rate of postoperative wound infection, in clean cases with the use of ilmplant and analyse the factors responsible for surgical site infection. Study Design: Prospective / descriptive study Place and Duration of Study: This study was conducted at the Department of Orthopedic Surgery, Peoples University of Medical & Health Sciences (PUMHS) Nawabshah from July 2015 to June 2017. Materials and Methods: Five hundred twenty cases were operated during two years, 26 developed infection. Patients of close fractures of long bones, immune competent, non diabetic, infection free, with age more than 10 years of either sex in which implants were used, included in this study. The cases on steroid therapy and chemotherapy were excluded from this study. Results: Out of 520 cases operated during two years, 26 developed inflection, infection rate was 5%. The most common organism isolated was staphylococcus aureus in 18(69.2%) cases. Infected cases above 60 years of age were 18(69.2%) in 3(11.5%) patients, cause was unstable and insecure fixation, 5(19.2%) cases were infected due to the prolong operative time (more than two hours), 5(19.2%) cases had pre-operative stay in the ward (longer than two weeks). Conclusion: In our setup the postoperative wound infection in clean Orthopaedic implant cases is much higher than International standards. Therefore, it should be controlled by early diagnosis, management and by eliminating the common factors responsible for postoperative wound infection.